INTEGRATING IEEE 802.11 AND LORAWAN FOR WIRELESS SENSOR NETWORK DATA TRANSACTION IN NON-INFRASTRUCTURE AREA - Stephanie I. Pella; Hendro FJ Lami (Jurnal Media Elektro, 2023)
This research aims to develop a system that integrates the IEEE 802.11 network and LoRa WAN in developing a wireless sensor network (WSN) in an area without public communication infrastructure. The sensor nodes were developed using ESP 8266 Node MCU with embedded IEEE 802.11 module and the sink was developed using Raspberry Pi minicomputer with LoRa module. The frames sent by sensor nodes were classified into regular data and critical data. The sensing data is forwarded by the sink to the nearest location with internet access using LoRaWAN according to their priority. Each node sent its regular frames with an interarrival time that varies from 30 seconds to 3 minutes and critical frames with an interarrival time of 1 to 5 seconds. The result shows that the delay of the network sending solely regular frames varies from 16.4 s to 602 and the delay of the network sending solely critical frames varies from 0.32 t0 1 s. When some nodes in the network send the regular frames and the other nodes send the critical frames, the delay of the regular frames drops to 1.25-1.75 s. The packet delivery rate of the system is 100%.